2016
DOI: 10.3174/ajnr.a4787
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of MRI Brain Injury Findings with Neonatal Clinical Factors in Infants with Congenital Diaphragmatic Hernia

Abstract: Most infants with congenital diaphragmatic hernia have at least 1 abnormality identified on MR imaging of the brain performed before discharge. The main predictors of brain injury in this population are a requirement for extracorporeal membrane oxygenation, large diaphragmatic defect size, and lack of oral feeding at discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
0
16
0
2
Order By: Relevance
“…A composite postnatal brain injury score was obtained to include ventriculomegaly; extra-axial space enlargement; injury to the cortex, white matter, and basal ganglia; and intraventricular, parenchymal, and cerebellar hemorrhage on a system modified by previous work by Danzer et al 3,12 and Tracy et al 5 and published by our group (Table 1). 1 Markers of CDH severity, including lung volumes, side of CDH, the presence of intrathoracic liver, and the presence of congenital heart disease (from the patient's chart) were recorded.…”
Section: Image Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A composite postnatal brain injury score was obtained to include ventriculomegaly; extra-axial space enlargement; injury to the cortex, white matter, and basal ganglia; and intraventricular, parenchymal, and cerebellar hemorrhage on a system modified by previous work by Danzer et al 3,12 and Tracy et al 5 and published by our group (Table 1). 1 Markers of CDH severity, including lung volumes, side of CDH, the presence of intrathoracic liver, and the presence of congenital heart disease (from the patient's chart) were recorded.…”
Section: Image Reviewmentioning
confidence: 99%
“…[1][2][3][4][5][6] We and other investigators have shown that postnatal factors in the neonatal intensive care unit, including the use of extracorporeal membrane oxygenation, the need for inotropes, lack of oral feeding at discharge, and placement of a gastrostomy tube before hospital discharge are associated with evidence of brain injury on MR imaging. 1,6,7 In addition, a large diaphragmatic defect, persistent pulmonary hypertension, and the presence of liver herniation into the chest are associated with a greater degree of brain injury postnatally. 5 Despite evidence of postnatal brain injury in these infants, the presence and extent of brain injury in utero are unclear.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Современные успехи реаниматологии, неонатологии и детской хи-рургии в последние десятилетия определили возмож-ность оказания неотложной помощи новорожден-ным детям с тяжелыми пороками развития. Тяжесть состояния таких детей при рождении зачастую обу-словлена легочно-сердечной недостаточностью, не-стабильной гемодинамикой, что повышает риск пе-ринатального поражения ЦНС [1][2][3].…”
unclassified
“…Помимо более высокой сте-пени детализации анатомических структур головного мозга, этот метод характеризуется отсутствием луче-вой нагрузки на организм, возможностью исследо-вания в различных плоскостях, не перемещая паци-ента, и высоким тканевым контрастом. Кроме того, МРТ является стандартизованным воспроизводимым методом, что делает его более объективным по срав-нению с другими видами нейровизуализации, вклю-чая нейросонографию [9][10][11][12]. Недостатком метода является необходимость специальной подготовки пациента (транспортировка, дополнительная меди-каментозная седация, необходимость магнит-совме-стимого кувеза для критически тяжелых новорожден-ных и др.)…”
unclassified